SIFAT ANTI RAYAP KATEKIN DARI GAMBIR (Uncaria gambir Roxb.) - Nandika, Dodi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Gambir is a dry extract from the leaves and branches of the Uncaria gambir Roxb plant. Its contains catechin that are quite large and have antioxidant properties. Catechin are flavonoid compounds contained in gambir (Uncaria gambir Roxb). Some previous studies have shown that catechins have antibacterial and antifungal properties. However, the antitermitics properties of these compounds have not been reported comprehensively. Preliminary research on the antitermitics properties of catechins was carried out by dissolving catechin in ethyl acetate (concentrations of 5%, 10%, 15%, and 20%) then applied to whatmann filter paper. Further research was carried out by impregnating catechin solutions (2.5%, 5% and 7.5% concentrations) into the rubber wood (Hevea brasiliensis) samples using the vacuum press method. The antitermitics properties was carried out based on the Japanese Industrial Standard (JIS) K-1571-2004 while testing the antitermitics properties of dry wood based on the Indonesian National Standard (SNI) 01-7207-2014. The results of the preliminary study showed that application of catechin had a significant effect on feedingpreferenceand mortality of termites C. curvignathusand C. cynocephalus.